2018
DOI: 10.1039/c8nr01512k
|View full text |Cite
|
Sign up to set email alerts
|

An immunoconjugated up-conversion nanocomplex for selective imaging and photodynamic therapy against HER2-positive breast cancer

Abstract: Photodynamic therapy represents a very attractive therapeutic tool considered to be effective, minimally invasive and minimally toxic. However, conventional photodynamic therapy actually has two main constraints: the limited penetration depth of visible light needed for its activation, and the lack of selectivity. Considering this, this work reports the synthesis and evaluation of a novel nanoconjugate for imaging and selective photodynamic therapy against HER2-positive breast cancer, a particularly aggressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 49 publications
1
30
0
2
Order By: Relevance
“…An additional avenue of HER2-positive cancer imaging is the use of nanoconjugates, which involves linking bioconjugates to nanoparticles (NPs) for delivery into cancer cells. A previous study has demonstrated the specific detection of only HER2-positive cells in vitro using the HER2-positive SKBR3 human breast cancer cell line [120]. This opens avenues for further research into PDD of HER2-positive tumors.…”
Section: Human Epidermal Growth Factor Receptormentioning
confidence: 76%
“…An additional avenue of HER2-positive cancer imaging is the use of nanoconjugates, which involves linking bioconjugates to nanoparticles (NPs) for delivery into cancer cells. A previous study has demonstrated the specific detection of only HER2-positive cells in vitro using the HER2-positive SKBR3 human breast cancer cell line [120]. This opens avenues for further research into PDD of HER2-positive tumors.…”
Section: Human Epidermal Growth Factor Receptormentioning
confidence: 76%
“…After 28 days of a double PDT application, mice injected with MNPs(MC540)/DSPE-PEG-NPY showed no tumor growth [151]. In a study performed by Ramírez-García et al (2018), a UCNP nanoconjugate was constructed for the targeted PDT and imaging against HER-2-positive BC cells, as well as to try and overcome the limited tumor cell depth penetration visible light has [152]. NaYF4:Yb,Er UCNPs were fabricated and attached to a zinc tetracarboxyphenoxy phthalocyanine (ZnPc) PS and a trastuzumab (Tras) HER-2 specific monoclonal antibody to form a UCNPs-ZnPc-Tras nanocomposite [152].…”
Section: Upconversion Nanoparticlesmentioning
confidence: 99%
“…In a study performed by Ramírez-García et al (2018), a UCNP nanoconjugate was constructed for the targeted PDT and imaging against HER-2-positive BC cells, as well as to try and overcome the limited tumor cell depth penetration visible light has [152]. NaYF4:Yb,Er UCNPs were fabricated and attached to a zinc tetracarboxyphenoxy phthalocyanine (ZnPc) PS and a trastuzumab (Tras) HER-2 specific monoclonal antibody to form a UCNPs-ZnPc-Tras nanocomposite [152]. The covalent bonds between UCNPs and ZnPc resulted in resonance energy transfer from the NPs to the PS, which in turn produced cytotoxic singlet oxygen and higher 1 O2 quantum yields when compared to control groups [152].…”
Section: Upconversion Nanoparticlesmentioning
confidence: 99%
“…Más aún, es posible utilizar nanocomplejos de diferentes colores permitiendo desarrollar sistemas multiplexados capaces de detectar más de un complejo de interés. Con esta técnica, recientemente se ha reportado la detección de Vaspin, una proteína presente en la sangre que puede causar diabetes tipo 2, en concentraciones tan bajas como 35 pg/ml (Ali et al, 2017) Fuente: Información detallada para la síntesis de este tipo de NPs puede encontrarse en: G. Ramírez-García et al (2018.…”
Section: Fluorescenciaunclassified
“…En el ámbito terapéutico, los nanomateriales han sido ampliamente utilizados en terapia fotodinámica, terapia fototérmica y como acarreadores de fármacos o nanovectores (Huang et al, 2006;Gobin et al, 2007;Ramírez-García et al, 2018;Zhou et al, 2017). Más recientemente se han venido desarrollando complejos teranósticos que combinan detección, imagen y terapia permitiendo también monitorear el efecto de la misma Lammers et al, 2011;Bai et al, 2015;Gobin et al, 2007;Ramírez-García et al, 2018;Zhou 13(24), 1e-24e, enero-junio 2020 | http: //dx.doi.org/10.22201/ceiich.24485691e.2020.24.69618 Elder De la Rosa, Gonzalo Ramírez, Sandeep Panikar, Tanya Camacho, Pedro Salas, Tzarara López-Luke et al, 2017. Estos complejos prometen la implementación de una medicina personalizada y preventiva aprovechando la alta sensibilidad de las técnicas de detección ya discutidas.…”
Section: Nanomedicinaunclassified